A modified algorithm with lipoprotein(a) added for diagnosis of familial hypercholesterolemia. Issue 10 (22nd August 2019) - Sun, Di; Cao, Ye‐Xuan; Li, Sha; Guo, Yuan‐Lin; Wu, Na‐Qiong; Gao, Ying; Dong, Qiu‐Ting; Liu, Geng; Dong, Qian; Li, Jian‐Jun
Abstract: Background: Previous studies have observed that high level of lipoprotein (a) [Lp(a)] was common in the phenotypic familial hypercholesterolemia (FH) and may explain part of the clinical diagnosis of FH. Hypothesis: We aim to develop a modified model including Lp(a) and compare its diagnostic performance with Dutch Lipid Clinic Network (DLCN) criteria. Methods: Data of 10 449 individuals were utilized for the model establishment (7806 for derivation and 2643 for validation) from January 2011 to March 2018. The novel score model was modified on the basis of DLCN. Furthermore, 718 patients were screened for LDLR, APOB, and PCSK9 gene mutations. Results: The novel modified model consisted of untreated low‐density lipoprotein cholesterol (LDL‐C) level, Lp(a), personal premature coronary heart disease (CHD), tendon xanthomas and family history of CHD and/or hypercholesterolemia. It has shown high discrimination (area under curve [AUC] 0.991, 95% confidence interval [CI[ 0.988‐0.994, P  < .001) for distinguishing clinical FH from non‐FH diagnosed using DLCN. Furthermore, a concordance analysis was performed to compare the modified model with DLCN and it showed a good agreement with DLCN ( κ = 0.765). External validation of the novel model also showed good accordance ( κ = 0.700). Further genetic analysis showed that the agreements between the new model and mutation improved a little compared to that between DLCN and mutation. Conclusions: The novel modified model, including Lp(a), could provide new insights into FH diagnosis in Chinese population with more concerns on the patients with high level of Lp(a).